Aboriginal women have a higher risk of cervical abnormalities at screening; South Australia, 1993–2016. (June 2019) - Li, Ming; Roder, David; Whop, Lisa J; Diaz, Abbey; Baade, Peter D; Brotherton, Julia ML; Canfell, Karen; Cunningham, Joan; Garvey, Gail; Moore, Suzanne P; O'Connell, Dianne L; Valery, Patricia C; et al.
Objective: Cervical cancer mortality has halved in Australia since the national cervical screening program began in 1991, but elevated mortality rates persist for Aboriginal and Torres Strait Islander women (referred to as Aboriginal women in this report). We investigated differences by Aboriginal status in abnormality rates predicted by cervical cytology and confirmed by histological diagnoses among screened women. Methods: Using record linkage between cervical screening registry and public hospital records in South Australia, we obtained Aboriginal status of women aged 20–69 for 1993–2016 (this was not recorded by the registry). Differences in cytological abnormalities were investigated by Aboriginal status, using relative risk ratios from mixed effect multinomial logistic regression modelling. Odds ratios were calculated for histological high grade results for Aboriginal compared with non-Aboriginal women. Results: Of 1, 676, 141 linkable cytology tests, 5.8% were abnormal. Abnormal results were more common for women who were younger, never married, and living in a major city or socioeconomically disadvantaged area. After adjusting for these factors and numbers of screening episodes, the relative risk of a low grade cytological abnormality compared with a normal test was 14% (95% confidence interval 5–24%) higher, and the relative risk of a high grade cytological abnormality was 61% (95% confidence interval 44–79%) higher, for Aboriginal women. The adjusted odds ratio of a histological high grade was 76% (95% confidence interval 46–113%) higher. Conclusions: Ensuring that screen-detected abnormalities are followed up in a timely way by culturally acceptable services is important for reducing differences in cervical cancer rates between Aboriginal and non-Aboriginal women.